Pelaksanaan Kegiatan Penyuluhan dalam Mendorong Kemandirian Ekonomi Pelaku UMKM melalui Optimalisasi Potensi Lokal di Desa Kepoh (Indonesian Version) - M. Ilham Wira Pratama; Nelly Astuti; Rendi Rendi (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
This activity aims to encourage the economic independence of Micro, Small, and Medium Enterprises (MSMEs) by optimizing local potential in Kepoh Village, Toboali District, South Bangka Regency. The outreach activities were conducted by collecting primary data through observation, interviews, and documentation regarding the condition of MSMEs and the village's superior potential, including the marine and fisheries, plantation, and mining sectors. The data obtained showed that the majority of MSMEs in Kepoh Village are engaged in the food trade and home industries, with varying income levels, ranging from Rp. 150,000 to Rp. 30,000,000 per month. In addition, the village's abundant potential, such as fisheries with an average production of 16.5 tons, plantations with various commodities, and tin mining resources, presents a great opportunity to support the development of local MSMEs. Through this outreach activity, MSMEs are encouraged to increase their business capacity, utilize local potential sustainably, and understand the importance of protecting Intellectual Property Rights (IPR) as a marketing strategy and to increase competitiveness. This counseling is carried out to provide a positive contribution in providing knowledge, motivation, and more innovative business management strategies starting from product marketing strategies both in economic and legal aspects as well as the urgency of business legality, so as to strengthen the economic independence of MSME actors and support the inclusive economic development of Kepoh Village